Exploring the Effects of Metabolites from Lactobacillus rhamnosus GM020 and Cyanidin-3-O-Glucoside on Differential Metabolites in the High-fat Diet Mice Liver Based on Metabolomics - Sihang WANG; Bin LI; Hui TAN; Xianjun MENG; Yongping XU; Shuying LI; Xiaoru LIU; Yuehua WANG; Yan MA (Shipin gongye ke-ji)
Objective: Investigating the regulatory effects of cyanidin-3-O-glucoside (C3G) and Lactobacillus rhamnosus GM020 metabolite (C3G-GM020) on cholesterol metabolism in high-fat diet-fed mice using untargeted metabolomics. Methods: C57BL/6 male mice were randomly divided into four groups: Normal control (NC) group, high-fat diet (HFD) group, low-dose C3G-GM020 group (50 mg/kg·d), and high-dose C3G-GM020 group (100 mg/kg·d). C3G-GM020 diet intervention was administered to high cholesterol model mice for 6 weeks. A widely targeted metabolomics approach was employed to analyze differential metabolites in mice liver. PCR method and reagent kits were employed to analyzed the bile acid synthesis pathway key genes expression and liver bile acid content, respectively. Results: A total of 43 different metabolites were identified between the NC and HFD group, among which 12(S)-HpETE, 13,14-dihydro-15-keto-PGE2, 5-aminopentanoic acid, corticosterone, 2-methoxyestradiol, threonic acid and other metabolites were reversed after C3G-GM020 intervention. KEGG pathway enrichment analysis showed that C3G-GM020 might regulate cholesterol metabolism by regulating the bile secretion pathway. The upregulation of cholesterol-7α-hydroxylase (CYP7A1) mRNA expression induced by high-fat diet was significantly (P<0.05) inhibited by C3G-GM020 intervention, while the expression of 25-hydroxycholesterol-7α-hydroxylase (CYP7B1) mRNA was promoted. Additionally, liver bile acid contents were increased, and liver farnesol X receptor (FXR) gene expression was significantly (P<0.05) upregulated. Conclusion: Intervention with C3G-GM020 was found to alter liver metabolites in mice, possibly through regulation of the bile acid secretion pathway to modulate cholesterol metabolism. Additionally, synthesis of bile acids via alternative pathways in hepatic cholesterol metabolism was promoted, leading to improved cholesterol homeostasis.